Literasi Keuangan dan Tingkat Pendidikan Terhadap Perencanaan Keuangan UMKM Pangan Jalan Payakumbuh Jakarta Selatan - Naser, Haspul; Kusuma Devi, Nurwulan; Herviana Rahmayati , Suci (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Background: MSMEs in the food sector show an important role in backup the Indonesian economy. However, financial planning challenges are often an obstacle to the sustainability of MSME businesses. Low financial literacy and formal education can hinder financial planning, resulting in suboptimal management and potentially threatening business continuity. Research objectives: The present research examines the impact of financial literacy and education level on the financial planning of MSMEs in the food sector in South Jakarta. Novelty: This study provides novelty by focusing on the combination of these two variables in the specific context of food sector MSMEs, which has rarely been explored in previous research. Research methodology: Quantitative approach with survey technique. The questionnaires distribute to 100 MSMEs in South Jakarta. Findings: The study reveals that financial literacy positively impacts MSMEs’ financial planning practices, while education level also has a positive but not significant impact. Conclusion: Financial literacy positively impacts MSMEs’ financial planning, with improved education and financial literacy contributing to better cash management and investment planning, highlighting the importance of financial literacy programs.